2013
DOI: 10.1128/aem.02521-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phenotypic Plasticity among Multihost Campylobacter jejuni and C. coli Lineages, Obtained Using Ribosomal Multilocus Sequence Typing and Raman Spectroscopy

Abstract: g Closely related bacterial isolates can display divergent phenotypes. This can limit the usefulness of phylogenetic studies for understanding bacterial ecology and evolution. Here, we compare phenotyping based on Raman spectrometric analysis of cellular composition to phylogenetic classification by ribosomal multilocus sequence typing (rMLST) in 108 isolates of the zoonotic pathogens Campylobacter jejuni and C. coli. Automatic relevance determination (ARD) was used to identify informative peaks in the Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…adenine, thymine, guanine), while peaks at 1123 and 1580 cm −1 referred to C-C stretching and CH 3 /CH 2 twisting or bending respectively which exist widely in carbohydrates, proteins and lipids ( Table S1, ESI †). The laser (532 nm) used in this study was shown to enhance the Raman signal of cytochrome c by resonance in other organisms 16, 17 . As a highly conserved heme protein, cytochrome c can also be found in P. aeruginosa .…”
mentioning
confidence: 97%
“…adenine, thymine, guanine), while peaks at 1123 and 1580 cm −1 referred to C-C stretching and CH 3 /CH 2 twisting or bending respectively which exist widely in carbohydrates, proteins and lipids ( Table S1, ESI †). The laser (532 nm) used in this study was shown to enhance the Raman signal of cytochrome c by resonance in other organisms 16, 17 . As a highly conserved heme protein, cytochrome c can also be found in P. aeruginosa .…”
mentioning
confidence: 97%
“…This approach has formed the basis of many recent investigations of the cryptic epidemiology of these organisms (Lang et al 2010;Müllner et al 2010;Thakur et al 2010;Hastings et al 2011;Jorgensen et al 2011;Kittl et al 2011;Magnú sson et al 2011;Sheppard et al 2011a,b;Sproston et al 2011;Read et al 2013) and will be the focus of this review. Such studies have included molecular epidemiological and evolutionary analyses and, in the past 15 years or so, the application of high-throughput DNA sequencing technologies of increasing capacity has enhanced the integration of these two areas of investigation to their mutual benefit.…”
mentioning
confidence: 99%
“…The peaks at 785 and 1340 cm À 1 , assigned respectively to pyrimidine and to aromatic vibration of DNA bases [55], are more pronounced in the red spectrum, thus supporting the hypothesis that the red area is related to the cell nucleus. On the other hand the green spectrum exhibits marked peaks at 750, 1130, 1316, 1585 cm À 1 , which are assigned to (in the same order) mitochondria, CytC, Histidine (within CytC), and CytC [56]. All these assignments are compatible with mitochondria and cellular respiration (CytC is well-known involved in respiration inside the mitochondria) [57,58].…”
Section: Raman Spectroscopy Inspection Of the Cellsmentioning
confidence: 92%